2009
DOI: 10.1128/cvi.00314-09
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-Derived Interleukin-10 Depresses the Bordetella pertussis - Specific Gamma Interferon Response in Vaccinated Infants

Abstract: Antigen-specific gamma interferon (IFN-␥) has been demonstrated to participate in protection againstBordetella pertussis infection. Circulating mononuclear cells from B. pertussis-infected and from pertussisvaccinated infants secrete high amounts of IFN-␥ after in vitro stimulation by B. pertussis antigens, but with a large variation in the secreted IFN-␥ levels between individuals. We show here that the inhibition of the specific IFN-␥ response can be at least partially attributed to IL-10 secretion by monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…IL-10 has been shown to dampen inflammatory cytokine responses to B. pertussis (49). Dirix et al recently reported that peripheral blood mononuclear cellderived IL-10 depresses B. pertussis-specific IFN-␥ production in vaccinated infants, further supporting the role of IL-10 in controlling B. pertussis-specific inflammatory cytokine responses (18). These data suggest that during B. pertussis infection, IL-1R contributes to the induction of IL-10, which is important for controlling inflammatory responses.…”
Section: Discussionmentioning
confidence: 95%
“…IL-10 has been shown to dampen inflammatory cytokine responses to B. pertussis (49). Dirix et al recently reported that peripheral blood mononuclear cellderived IL-10 depresses B. pertussis-specific IFN-␥ production in vaccinated infants, further supporting the role of IL-10 in controlling B. pertussis-specific inflammatory cytokine responses (18). These data suggest that during B. pertussis infection, IL-1R contributes to the induction of IL-10, which is important for controlling inflammatory responses.…”
Section: Discussionmentioning
confidence: 95%
“…IL-10 is an antiinflammatory cytokine that is involved in dampening the production of both TNF-␣ and IFN-␥ (16,44). In previous studies, the induction of IL-10 has been associated with the presence of the Yersinia T3SS-secreted protein LcrV (9,14).…”
Section: Discussionmentioning
confidence: 99%
“…Infants most often are considered relatively deficient in their capacity to secrete gamma interferon (IFN-␥) (19,25). However, some exceptions have been reported, including the ability to secrete IFN-␥ in response to the major B. pertussis antigens during infection (14) or after vaccination (13,5), indicating that infants are able to mount both antibodyspecific and antigen-specific IFN-␥ responses upon the infection or administration of pertussis vaccines.…”
mentioning
confidence: 99%